Comparison of PSO and de for truck scheduling in multi-door cross docking terminals - W. Wisittipanich (2018)
© 2017 IEEE. This paper presents an application of the modified version of Differential Evolution, call 2-Stage DE (2S-DE), for solving the transshipment of multiple product types in a multi-door cross docking system when a storage is allowed to be temporarily hold at the shipping dock. The objective is to find the truck schedule that minimizes the makespan. The performances of the proposed 2S-DE are evaluated and compared with the original DE and the GLNPSO previously published in literature. Using a set of generated instances, the experimental results show that all algorithms are able to find optimal solutions in small-size problems easily. However, when the problem becomes more complex, 2S-DE is superior to the GLNPSO and the original DE since it statistically shows outstanding results in terms of solution quality and convergence behavior.